Delays in the diagnosis and treatment of muscle invasive bladder cancer: A pilot project mapping the pathway. (July 2015) - Iqbal, M Shahid; Pickles, R; Pedley, I; Frew, J; Azzabi, A; Heer, R; Thorpe, A; Johnson, M; Robson, L; McMenemin, R
Background: The patient pathway for muscle invasive bladder cancer (MIBC) is multidisciplinary. Trans-urethral resection of bladder tumour (TURBT) counts as the first definitive treatment and subsequent definitive therapy thereafter is often delayed, which may adversely affect outcome. We elected to scrutinise the management pathway in detail to understand these delays and improve the patient experience. Method: A retrospective mapping analysis was conducted on 17 patients with MIBC. The causes of any delays and measures to avoid these were identified. A prospective study of 17 patients with MIBC was then undertaken to see if the strategies used to re-engineer the patient care pathway had been effective. Result: The median time from GP referral to first appointment was 9 days (range: 1–37) and from TURBT to subsequent radical treatment was 75 days (range: 27–105) in keeping with published literature. The median time for a referral letter from urology to oncology following MDT was 15 days. We therefore modified the MDT proforma to use as a formal referral, and a project manager proactively managed the patient pathway. Capacity issues were addressed by protecting clinical slots for bladder patients and establishing monthly evening clinics. After implementing the strategies, the median days from first appointment to TURBT improved from 31 to 23 days and time from TURBT to subsequent treatment improved from 75 to 66 days. The time from MDT referral to being seen by an oncologist or urologist significantly reduced from 32 to 15 days. Conclusion: Retrospective analysis identified delays between initial TURBT to definitive therapy and strategies adopted to reduce these were effective. TURBT is a diagnostic process and if acknowledged as first treatment results in delays of what is the definitive treatment. We found the initial diagnostic pathway to work well but non-muscle invasive bladder cancer (NMIBC) and MIBC are then managed very differently and warrant two separate pathways.